Penerapan Kebijakan Tingkat Komponen Dalam Negeri (TKDN) Terhadap Pengembangan Industri Alat Kesehatan - Nova, Lilian Susanti; Puspitasari, Dwi Anggreni; Febriani, Febriani (JURNAL BIDANG ILMU KESEHATAN, 2025)
The Domestic Component Level (TKDN) is a value that indicates the percentage of domestic goods/services used in a product. The purpose of this study is to examine the implementation of TKDN policies to the development of the Medical Devices industry. This study was conducted using a qualitative methods, with in-depth interview data collection techniques, invoving a sample of 10 medical device companies, Duscussions and field confirmations were held with the relevant companies, and a literature riview on medical device industry development policies was also performed. The study took place from Aprill to December 2022. The results of this study indicate that the majority of industries believe their production capacity is sufficient to meet domestic market needs. Companies are still focused on fulfilling domestic medical device needs and have not yet engaged in exporting products. Human resources show that Indonesia can enhance its human resources and technology. Companies have Research and Development (R&D) programs, and some companies, such as Domestic Investment Companies (PMDN), colaborate with universities, agencies or government research institutions for R&D effort. In conclusion, there is a need for improvement in TKDN regulations, such as determining tariffs and CSR level according to the size of the companies (medium and large), additionally there should be an increase in the number of companies involved in TKDN, enchanced promotional opportunities between regions and contries, and the provision of exhibitions and business matching event with neighboring countries coordinated by the government. The government should also support the availability of information/data related to the medical devices needs required for short and medium term programs.